Conceptualising effective symptom management in palliative care: a novel model derived from qualitative data - Emma J. Chapman; Simon Pini; Zoe Edwards; Yousuf Elmokhallalati; Fliss E. M. Murtagh; Michael I. Bennett (BMC Palliative Care, 2022)
Abstract Background Pain, breathlessness and fatigue are some of the most challenging symptoms to manage in patients with advanced disease. Specialist palliative care leads to better symptom management, but factors contributing to successful symptom management in this context have not been explored. Our aim was to understand what facilitates effective symptom management in specialist palliative care within UK hospices and investigate what barriers are experienced. Methods This was a grounded theory study using qualitative semi-structured focus groups and interviews. Participants were recruited from multidisciplinary specialist palliative care teams (doctors, nurses, healthcare assistants, physiotherapists, occupational therapists, complementary therapists, social workers and chaplains) working in inpatient, outpatient and community services provided by five hospices in the United Kingdom. Results We present a novel qualitative data-derived model of effective symptom management in specialist palliative care. We describe a co-ordinated, multi-faceted, sequential approach involving a process of engagement, partnership, decision-making, and delivery. Interventions to manage symptoms are less effective in psychologically distressed patients. Our data highlights that families of patients have a key role in determining effectiveness of symptom management interventions A holistic approach by a co-ordinated, multi-disciplinary team, including support to recognise and minimise psychological distress might facilitate more effective symptom management. Barriers to symptom management include team discordance and lack of understanding about symptom management by patient and families. Conclusions Shared decision-making between patients and professionals and co-ordination of care by a multi-disciplinary team are key components of effective symptom management. Actions to address psychological distress and evaluate the understanding and expectations of patients and their families would enable more effective symptom management. A more effective multi-disciplinary approach would be facilitated by discussion within teams about role competencies and boundaries.